Green tea extract and its major constituent, epigallocatechin-3-gallate, induce epithelial beta-defensin secretion and prevent beta-defensin degradation by Porphyromonas gingivalis - Lombardo Bedran, T. B. [UNESP]; Feghali, K.; Zhao, L.; Palomari Spolidorio, D. M. [UNESP]; Grenier, D. (Wiley-Blackwell, 2014)
Background and Objective: Antimicrobial peptides, such as beta-defensins, secreted by gingival epithelial cells, are thought to play a major role in preventing periodontal diseases. In the present study, we investigated the ability of green tea polyphenols to induce human beta-defensin (hBD) secretion in gingival epithelial cells and to protect hBDs from proteolytic degradation by Porphyromonas gingivalis.Material and Methods: Gingival epithelial cells were treated with various amounts (25-200 mu g/mL) of green tea extract or epigallocatechin-3-gallate (EGCG). The secretion of hBD1 and hBD2 was measured using ELISAs, and gene expression was quantified by real-time PCR. The treatments were also carried out in the presence of specific kinase inhibitors to identify the signaling pathways involved in hBD secretion. The ability of green tea extract and EGCG to prevent hBD degradation by proteases of P. gingivalis present in a bacterial culture supernatant was evaluated by ELISA.Results: The secretion of hBD1 and hBD2 was up-regulated, in a dose-dependent manner, following the stimulation of gingival epithelial cells with a green tea extract or EGCG. Expression of the hBD gene in gingival epithelial cells treated with green tea polyphenols was also increased. EGCG-induced secretion of hBD1 and hBD2 appeared to involve extracellular signal-regulated kinase 1/2 and p38 mitogen-activated protein kinase. Lastly, green tea extract and EGCG prevented the degradation of recombinant hBD1 and hBD2 by a culture supernatant of P. gingivalis.Conclusion: Green tea extract and EGCG, through their ability to induce hBD secretion by epithelial cells and to protect hBDs from proteolytic degradation by P. gingivalis, have the potential to strengthen the epithelial antimicrobial barrier. Future clinical studies will indicate whether these polyphenols represent a valuable therapeutic agent for treating/preventing periodontal diseases.
Keywords: beta-defensin; epigallocatechin gallate; epithelial cells; green tea; periodontal disease; Porphyromonas gingivalis